The Role of the Husbands via the Endorphin Massage on the Occurrence of Postpartum Blues in Primiparous Postpartum Mothers - Sulpat, Emuliana; Sulistyono, Agus; Yusuf, Ah.; Kusumaningrum, Andri Tri; Hariyanto, Susilo (International Journal of Psychosocial Rehabilitation, 2020)
The role of the husband’s is very necessary when it comes to helping the mother have an endorphin massage. The aim of this research is to determine the effectiveness of endorphin massages on primiparous postpartum mothers. A quasi-experimental design with a posttest approach only with a control group was used. The population consisted of postpartum mothers for 3-10 days. This research used total sampling to get 56 respondents. The population was divided into 2 groups, namely the case group and the control group. The case group was given a massage once a day everyday for 20 minutes. The treatment was done for 2 weeks. The control group wasn’t given a massage. The postpartum blues were measured using the Edinburgh Depression Postnatal Score (EPDS) questionnaire scale. The results of the data after tabulation were processed using an independent paired sample t-test. The results show that the postpartum blues of the mothers who had an endorphin massage were less severe than the blues of the mother who had not received an endorphin massage. The difference was 29,62 points. The results obtained a p value = 0.0001 and α <0.05, which obtained the result that there is impact from the endorphin massage on postpartum blues. An endorphin massage given by the husband is effective at reducing the rate of postpartum blues. Thus an endorphin massage can be used as an alternative to the postpartum mothers reducing their stress levels during lactation.